Morphology and chaetotaxy of the first instar larva of the scorpionfly Sinopanorpa tincta (Mecoptera: Panorpidae) - Chen, Hong-Min; Hua, Bao-Zhen (Zootaxa, 2011)
The morphology and chaetotaxy of the first instar larva of the scorpionfly Sinopanorpa tincta (Navás, 1931) are described and illustrated for the first time with the aid of light microscopy and scanning electron microscopy, with particular attention to the mouthparts and their sensilla. A comparison is made with the larvae of other known Mecoptera, especially Panorpa and Neopanorpa in Panorpidae.